Pedagogical Conditions for Developing Tolerance Among School Pupils Through Paralympic Education Tools - Saparniyazov Sansizbay Kadirniyazovish (Next Scientists International Journal EIJP, 2026)
This article examines the role of Paralympic education in developing tolerance among school pupils in inclusive educational environments. The study analyzes how adapted sports, athlete stories, interactive activities, and reflective discussions contribute to empathy, respect, equality, and positive attitudes toward people with disabilities. Qualitative and analytical methods were used in the research. The findings show that Paralympic education helps reduce stereotypes, improve social integration, and develop inclusive thinking among pupils. The study also emphasizes the importance of teacher competence and supportive classroom atmosphere in tolerance formation.